I’jaz Al-Qur’an : Memahami Aspek dan Kebenaran Al-Qur’an - Syam, Asriadi; Miswar, Andi; Sohrah, Sohrah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
Important ideas in Islam that support the veracity and divinity of Islamic teachings include Ijaz Al-Qur'an and Its Aspects. Ijaz Al-Qur'an alludes to the Qur'an's miraculous qualities, which demonstrate that Allah SWT revealed the sacred book of Islam rather than it being a human invention. The Qur'anic language's beauty and distinctiveness, its content's coherence and harmony despite being revealed over a 23-year period, and the historical and scientific facts that have been validated by contemporary scientific findings are the primary features of Ijaz. Even those who question the authenticity of the Qur'an are challenged by it to create a single surah that is comparable to it; this challenge has not yet been fulfilled. Keywords:  I’jaz, Miracle, Aspects, Al-Qur’an. Abstrak Ijaz Al-Qur'an dan Aspeknya adalah konsep penting dalam Islam yang menegaskan keaslian dan keilahian ajaran agama Islam. Ijaz mencakup kemukjizatan Al-Qur'an, yang menunjukkan bahwa kitab suci umat Islam bukanlah ciptaan manusia, melainkan wahyu dari Allah SWT. Aspek utama ijaz termasuk bahasa yang indah dan unik, kekonsistenan dan keselarasan isi meskipun diturunkan selama tiga puluh tiga tahun, dan bukti sejarah dan informasi ilmiah. Al-Qur'an bahkan menantang siapa saja yang mempertanyakan keasliannya untuk membuat surah yang mirip. Tantangan ini masih belum terselesaikan hingga saat ini.